Simulasi Model Evakuasi Bencana Kebakaran Pemukiman Pesisir - Sandana, Aprilla Warlisia (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
The poor setting out of coastal settlements had very high vulnerability of the fire hazard. The limited access caused difficulties in evacuating the community (agents) when fire was accured. The communities as agents in a group interaction activities due to the environment had evacuation path and other support systems to find the fastest way out. This research had designed a simulation model of community movement during a fire disaster in the coastal settlement. The case study of this research was defined in the dense coastal settlement area of Pasar ​​Batu Tarakan, North Kalimantan. The community evacuation simulation used the Agent Based Modeling (ABM) utilized NetLogo software. The survey was conducted by considering the condition of main route that can be accessed. The modeling had 3 simulation scenarios were based on the number of agents movement who left the fire site. The double linear regression had been utilized to analyze the variable correlation. The results showed a scenario 3 had the largest people number who passed out the exit way. The selection of the path was based on the distance and route width on the number of people save had very significant correlation (R2 = 98,34%).